Foundational and practical aspects of resource analysis 4th international workshop, FOPARA 2015, London, UK, April 11, 2015 : revised selected papers - Eekelen, Marko van; Dal Lago, Ugo (Springer, 2016)
This book constitutes the proceedings of the 4th International Workshop on Foundational and Practical Aspects of Resource Analysis, FOPARA 2015, held in London, UK, in April 2015. The 6 papers presented in this volume were carefully reviewed and selected from 7 submissions
Keywords: Informatik; Computer science; Computer system failures; Software engineering; Computer logic; Mathematical statistics; Computer simulation; Komplexitätsklasse; Kostenfunktion; Programmanalyse; Ressourcenbeschränktes Maß; Eingebettetes System; Abstrakte Interpretation; Konferenzschrift